2018
DOI: 10.1016/j.celrep.2018.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Active Maintenance of T Cell Memory in Acute and Chronic Viral Infection Depends on Continuous Expression of FOXO1

Abstract: SUMMARY Immunity following an acutely resolved infection or the long-term equipoise of chronic viral infections often depends on the maintenance of antigen-specific CD8+ T cells, yet the ongoing transcriptional requirements of these cells remain unclear. We show that active and continuous programming by FOXO1 is required for the functional maintenance of a memory population. Upon Foxo1 deletion following resolution of an infection, memory cells rapidly lost their characteristic gene expression, gradually decli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
87
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(91 citation statements)
references
References 47 publications
4
87
0
Order By: Relevance
“…Indeed, studies using the inducible deletion of FOXO1 after resolution of viral infection suggest that memory cells require continuous FOXO1 activity to maintain their survival and transcriptional programming. 250,251 Furthermore, P2RX7 activates AMPK and restrains mTOR activation to promote memory CD8 + T-cell function, and transient P2RX7 blockade at the memory stage compromises the maintenance of memory CD8 + T cells. 252 Together, these results indicate that memory CD8 + T-cell fate is not an entirely default program but is an active process requiring regulatory networks, such as mTORC1 and mTORC2 signaling, to fix their lineage maturation.…”
Section: Mtor Signaling In Effector-cell Maintenance and Transdiffementioning
confidence: 99%
“…Indeed, studies using the inducible deletion of FOXO1 after resolution of viral infection suggest that memory cells require continuous FOXO1 activity to maintain their survival and transcriptional programming. 250,251 Furthermore, P2RX7 activates AMPK and restrains mTOR activation to promote memory CD8 + T-cell function, and transient P2RX7 blockade at the memory stage compromises the maintenance of memory CD8 + T cells. 252 Together, these results indicate that memory CD8 + T-cell fate is not an entirely default program but is an active process requiring regulatory networks, such as mTORC1 and mTORC2 signaling, to fix their lineage maturation.…”
Section: Mtor Signaling In Effector-cell Maintenance and Transdiffementioning
confidence: 99%
“…23) have been considered essential for the formation of TE or conventional TEM cells, whereas Eomes(24), Bcl6(25,26), Foxo1(27)(28)(29), Stat3(26), and Id3(22,30) have been linked to the differentiation of MP or TCM(3). Here, we demonstrated that optimal formation of the redefined TEM population was not impaired by diminished T-bet or Blimp1 expression.…”
mentioning
confidence: 55%
“…We next examined the memory lineage-specifying roles of Bcl6 and Foxo1, transcription factors canonically recognized to support TCM formation relative to TEM (3,(25)(26)(27)(28)(29). As expected, loss of Bcl6 or or Foxo1 resulted in a loss of total memory P14 cells, including fewer TCM (blue bars) compared to control P14 cells ( Fig.…”
Section: Terminal-tem Possess Key Characteristics Of Memory T Cells Wmentioning
confidence: 67%
See 1 more Smart Citation
“…Loss of FOXO1 in these infections led to the loss of TCF7+ memory like cells . 135 The TCF7 + CD8 memory precursors in vivo in chronic infections and cancer were recently found to represent two distinct subpopulations of exhausted T cells, the TCF7+ PD1+ and TCF7-PD1 + . The TCF7+ PD1+ were found to be with stem cell like properties, and the cells responsible for generating proliferative burst with anti-PD1 immunotherapy mediating tumor control as well as control of chronic viral infections.…”
Section: Tcf1 Tcf7 and Foxo1mentioning
confidence: 99%